Reply - Huijbers, Anne (Reti Medievali Rivista, 2023)
This essay responds briefly to contributions by Éloïse Adde-Michel Margue, Étienne Doublier and Giovanni Francesco Contel discussing the volume Emperors and imperial discourse in Italy.